2013
DOI: 10.1016/j.ejvs.2012.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Provision of vascular surgery in England in 2012

Abstract: This study has shown that currently 80 trusts in England provide acute and elective arterial and aortic surgery with 48 centralised complex and arterial vascular services. An integrated vascular service will provide the best quality of care, develop the latest techniques and improve clinical standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…During the study, vascular surgery in Sweden was already carried out by vascular specialist centres. However, in England, pressures to centralize vascular surgery started around 2007, with initial processes starting around 2009 26,27 and further remodelling around 2013 28 . The present study showed that, through increased use of EVAR in England between 2007 and 2012, the difference in 90-day mortality between the two countries was abolished.…”
Section: Discussionmentioning
confidence: 99%
“…During the study, vascular surgery in Sweden was already carried out by vascular specialist centres. However, in England, pressures to centralize vascular surgery started around 2007, with initial processes starting around 2009 26,27 and further remodelling around 2013 28 . The present study showed that, through increased use of EVAR in England between 2007 and 2012, the difference in 90-day mortality between the two countries was abolished.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one article reported over 800 000 data relating to Clostridium difficile infections. However, this was the answer to a question, rather than obtaining 800 000 individual data points, so was not included in the number of data obtained 5 9. Finally, we had no way of assessing the quality of data collected.…”
Section: Discussionmentioning
confidence: 99%
“…Also, during our study period, in particular the years from 2010 to 2015, vascular services in the UK were subject to a process of specialisation away from general surgery, and centralisation from multiple low volume centres to a smaller number of high volume specialist centres. 17 It is possible that this reorganisation of vascular surgical care has had an impact on the changes and improvements identified in the current study. In response to increasing evidence pointing to a positive relationship between hospital and surgeon volumes and the outcome of arterial surgery 18 diagnosis and less complex interventions.…”
Section: Summary Of Main Findingsmentioning
confidence: 95%
“…A hub is a hospital that provides a vascular on-call rota of 1:6 or greater, and serves a population-base of at least 800 000. 17,19 Other possible explanations for the decreasing risks of amputation and death among PAD outcomes (coronary heart disease and stroke) have declined considerably in all UK countries 24,25 . The prevalence of CVD has, however, remained relatively static and slightly increased in men and women aged 65 years and older between 2004 and 2015, which Bhatnagar and colleagues hypothesise could be a result of the reduced mortality and case-fatality rates.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%